Electroconvulsive Therapy for Patients with Catatonia: Current Perspectives - Lloyd JR (Dove Medical Press, 2020)
Jenifer R Lloyd,1 Eric R Silverman,1 Joseph L Kugler,2 Joseph J Cooper1 1Department of Psychiatry, University of Illinois at Chicago, Chicago, IL, USA; 2Department of Psychiatry, University of Texas-Dell Medical School, Austin, TX, USACorrespondence: Jenifer R LloydDepartment of Psychiatry, University of Illinois at Chicago, 912 S Wood St (MC 913), Chicago, IL 60612, USATel +1 312-996-0906Fax +1 312-996-9517Email jlloyd5@uic.eduAbstract: Catatonia is a serious, common syndrome of motoric and behavioral dysfunction, which carries high morbidity and mortality. Electroconvulsive therapy (ECT) is the definitive treatment for catatonia, but access to ECT for the treatment of catatonia remains inappropriately limited. Catatonia is observable, detectable, and relevant to various medical specialties, but underdiagnosis impedes the delivery of appropriate treatment and heightens risk of serious complications including iatrogenesis. Current understanding of catatonia’s pathophysiology links it to the current understanding of ECT’s mechanism of action. Definitive catatonia care requires recognition of the syndrome, workup to identify and treat the underlying cause, and effective management including appropriate referral for ECT. Even when all of these conditions are met, and despite well-established data on the safety and efficacy of ECT, stigma surrounding ECT and legal restrictions for its use in catatonia are additional critical barriers. Addressing the underdiagnosis of catatonia and barriers to its treatment with ECT is vital to improving outcomes for patients. While no standardized protocols for treatment of catatonia with ECT exist, a large body of research guides evidence-based care and reveals where additional research is warranted. The authors conducted a review of the literature on ECT as a treatment for catatonia. Based on the review, the authors offer strategies and future directions for improving access to ECT for patients with catatonia, and propose an algorithm for the treatment of catatonia with ECT.Keywords: catatonia, electroconvulsive therapy, underdiagnosis, algorithm